Beam selection optimization algorithm for the Satcube Ku. - Olsson, Lucas; Saber, Pouria (My University, 2023)
The Satcube Ku is a satellite terminal which provides internet access to a user anywhere on Earth with the help of spot beam technology. For a given position on Earth, multiple intersecting beams will be present with varying signal strength. There is the need to distinguish one beam from another in order establish a hierarchy. The purpose of this master thesis is to investigate a way to rank the available beams at a position on Earth and develop that into a new beam selection algorithm for the Satcube Ku terminal. The new algorithm must address both circular and elliptical HTS-beams as the beams are projected across the surface of the Earth. There are many limitations to this project and many different approaches have been presented. The approach is to analyze user data and geospatial data combined with provided satellite information in order to find important aspects of the problem. A five step algorithm was ultimately decided. The algorithm takes the user position as an input and gives a sorted list from highest to lowest carrier-to-noise expected in that position as output. The steps are: Step 1: Position and all available beams, Step 2: Beamcenter of beams, Step 3: CNR value at beamcenter, Step 4: CNR reduction to the user posi tion, Step 5: CNR arranged list based on projection and accuracy. The step 1 was solved using polygon conversion of the beam contours given by the terminal and then calculating which polygons the user was inside of. In step 2 the beamcenter of the beams were estimated by measuring the distance from the polygon center to a beam center position provided by Intelsat for certain beams. In step 3 the each beamcenter was given a maximum theoretical value also provided by Intelsat. In step 4 three different methods were investigated to project what the received CNR would be at the user position. The methods were Concentric Contour Contraction, Concentric Elliptical Expansion and Least square fit method. The Concentric El liptical expansion was the most appropriate method available and was used in step 5 for a test position in Gothenburg. The resulting output was limited to only IS33 and IS37 satellites due to the lack of information regarding the beam center values. The final list projections compared to actual measurements performed within 1 dB.
Keywords: Satellite communication, Algorithm, Python, Data analysis, High-throughput satellite, Satcube Ku